Cycloid psychoses in the psychosis spectrum: evidence for biochemical differences with schizophrenia - van de Kerkhof N; Fekkes D; van der Heijden F; Hoogendijk W; Stöber G; Egger J; Verhoeven W (Neuropsychiatric Disease and Treatment)
Nora WA van de Kerkhof,1,2 Durk Fekkes,2,3 Frank MMA van der Heijden,1 Witte JG Hoogendijk,2 Gerald Stöber,4 Jos IM Egger,1,5,6 Willem MA Verhoeven1,2 1Vincent van Gogh Institute for Psychiatry, Centre of Excellence for Neuropsychiatry, Venray, 2Department of Psychiatry, 3Department of Clinical Chemistry, Erasmus University Medical Center, Rotterdam, The Netherlands; 4Department of Psychiatry, Psychosomatics and Psychotherapy, University of Würzburg, Würzburg, Germany; 5Behavioural Science Institute, 6Donders Institute for Brain, Cognition and Behaviour, Radboud University Nijmegen, Nijmegen, The Netherlands Abstract: Cycloid psychoses (CP) differ from schizophrenia regarding symptom profile, course, and prognosis and over many decades they were thought to be a separate entity within the psychosis spectrum. As to schizophrenia, research into the pathophysiology has focused on dopamine, brain-derived neurotrophic factor, and glutamate signaling in which, concerning the latter, the N-methyl-d-aspartate receptor plays a crucial role. The present study aims to determine whether CP can biochemically be delineated from schizophrenia. Eighty patients referred for psychotic disorders were assessed with the Comprehensive Assessment of Symptoms and History, and (both at inclusion and after 6 weeks of antipsychotic treatment) with the Positive and Negative Syndrome Scale and Clinical Global Impression. From 58 completers, 33 patients were diagnosed with schizophrenia and ten with CP according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, and Leonhard criteria, respectively. Fifteen patients were diagnosed with other disorders within the psychosis spectrum. At both time points, blood levels of the dopamine metabolite homovanillic acid, brain-derived neurotrophic factor, and amino acids related to glutamate neurotransmission were measured and compared with a matched control sample. Patients with CP showed a significantly better response to antipsychotic treatment as compared to patients with schizophrenia. In CP, glycine levels were elevated and tryptophan levels were lowered as compared to schizophrenia. Glutamate levels were increased in both patient groups as compared to controls. These results, showing marked differences in both treatment outcome and glutamate-related variable parameters, may point at better neuroplasticity in CP, necessitating demarcation of this subgroup within the psychosis spectrum. Keywords: cycloid psychoses, schizophrenia, glutamate, glycine, tryptophan, neuroplasticity